Attention Games : 101 Fun, Easy Games That Help Kids Learn to Focus - Sher, Barbara, 1943- (Hoboken, N.J. : Wiley ; Chichester : John Wiley [distributor], 2006)
Parents and teachers who are looking for ways to help all children develop healthy attention spans can use the fun, simple, and educational activities in this book to help kids learn how to stay focused.
Games for infants -- Games for 1- to 3-year-olds -- Games for 3- to 6-year-olds -- Games for 6- to 12- year-olds -- Games for teens.
Formerly CIP.
Includes index.
Keywords: Educational games; Attention in children